Additive impact of pneumococcal conjugate vaccines on pneumonia and empyema hospital admissions in England. Issue 4 (October 2015) - Saxena, Sonia; Atchison, Christina; Cecil, Elizabeth; Sharland, Mike; Koshy, Elizabeth; Bottle, Alex
Summary Objectives A wider spectrum 13-valent pneumococcal vaccine (PCV13) replaced PCV7 in the child immunization schedule in England from 2010. We assessed the additional impact of PCV13 over PCV7 on all-cause pneumonia and empyema admissions. Methods We extracted Hospital Episode Statistics data from 2001 to 2014 on all-cause pneumonia (ICD-10 codes J12-18) and empyema admissions (J86.0, J86.9) for children <16 years in England. Trend analysis and rate ratios (RR) were calculated comparing the Pre-vaccine era to September 2006, the PCV7 era and the PCV13 era from April 2010. Results Annual hospital admissions for pneumonia and empyema were increasing in the Pre-vaccine era peaking in 2005 at 15, 733 pneumonia and 382 empyema cases (158.6 and 3.9 per 100, 000 children, respectively). These rates fell following PCV7 introduction in 2006 but began to climb soon afterwards until PCV13 was introduced. By 2013, admission rates for pneumonia and empyema were 102.2 and 1.9 per 100, 000 children, respectively. We found no added benefit of PCV13 over PCV7 on pneumonia admissions following PCV13 introduction but there was a significant decrease in empyema admissions in children aged <2 years (RR 0.58; 95% CI 0.34–0.99). Conclusions Additional serotypes covered by PCV13 may be more important in the aetiology of empyema and invasive disease than as a cause of uncomplicated pneumonia.